2011
DOI: 10.1590/s0102-09352011000200021
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de vacas leiteiras à substituição parcial de farelo de soja por ureia encapsulada

Abstract: RESUMOAvaliou-se a substituição parcial de farelo de soja na dieta-controle por ureia encapsulada ou por ureia, ambos acrescidos de polpa cítrica. Dezoito vacas foram alocadas a uma sequência de três tratamentos, em seis quadrados latinos 3x3, com períodos de 21 dias. O teor de proteína bruta nas dietas foi 15,5%, cerca de 1,5% oriundo de nitrogênio não proteico (NNP). O uso de NNP reduziu o consumo diário de matéria seca em 0,8kg (P=0,04), sem influenciar a produção de leite (31,5kg, P=0,98). A conversão do a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
4
16
1
3
Order By: Relevance
“…Regarding the digestibility of NDF, the results obtained in the present study are similar to those observed by some authors (Galo et al, 2003;Azevedo et al, 2008;Santos et al, 2011), who did not detect effects of treatments using slowrelease urea on the digestibility of NDF either.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the digestibility of NDF, the results obtained in the present study are similar to those observed by some authors (Galo et al, 2003;Azevedo et al, 2008;Santos et al, 2011), who did not detect effects of treatments using slowrelease urea on the digestibility of NDF either.…”
Section: Discussionsupporting
confidence: 92%
“…The urea physically encapsulated by vegetable waxes is aimed at reducing the speed of ammonia release into the rumen (Santos et al, 2011). This type of urea has been tested in some experiments with dairy cows (Galo et al, 2003;Akay et al, 2004;Souza et al, 2010;Santos et al, 2011;Sinclair et al, 2012). However, the efficiency of this product must be evaluated in diets for crossbred cows with average milk yield.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, products that aim at the control of the release of non-protein nitrogen (NPN) in the rumen have been developed so as to improve the efficiency of transformation of nitrogen into microbial protein (Akay et al, 2004). According to Santos et al (2011), the replacement of feeds that contain true protein by feeds with a higher content of non-protein nitrogen, such as urea, can improve the financial efficiency of feeding and reduce the need to purchase protein contents. Moreover, it allows for the formulation of diets with greater inclusion of energy feeds, fibrous by-products and forages.…”
Section: Introductionmentioning
confidence: 99%
“…The roughage utilized was sugarcane (Saccharum officinarum) variety RB 72454, treated with 1% of a mixture of urea and ammonium sulfate (9:1) in the experimental phase. Following the recommendations of Santos et al (2011), for a period of seven days before the onset of the experiment, cows received the roughage containing only 0.5% of the mixture of urea aiming to acclimate to this ingredient added to the roughage. The concentrate supplementation level was defined by the isoproteic and isoenergetic balance of the diets according to NRC (2001) to meet the requirements for maintenance, a body weight gain of 0.15 kg/day, and production of 15 kg milk/day (Table 1).…”
Section: Methodsmentioning
confidence: 99%